Environmental Politics Through the Use of Social Media to Spread the Issue of Climate Change and Land Fires - Elyta; Ratu Zahira Lutfie; Arissy Jorgi Sutan (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2024)
Social media is employed in various acts, one of which is related to social movements, as in the example of social movements against climate change that use social media. This study seeks to understand the social media used in the climate change social movement that occurred on social media. This research's value and analysis portion was delivered through a descriptive narrative and a qualitative technique. This study also used qualitative data analysis software (Q-DAS) to learn about the trends in social media conversations and themes. Twitter was the social media platform employed in this study. This study addresses the following question: Q1 What kind of relevant climate change theme is spreading on social media? Q2 Explain the role of hashtags in the climate change debate. Q3 What is the nature of the narrative that has propagated on social media about climate change subjects, and how relevant is it? Q4: How does climate change affect social movements from the standpoint of Green Politics? The findings of this study are as follows: 1.) The climate change topic gained traction on social media. The narrative in this example avoided utilizing hashtags to promote and provide information about climate change talks. 2.) There is still a link between the hashtags for climate change talks on social media. 3.) The narration on the climate change topic is dominating, with hashtags used to ensure that the narration spreads and that netizens pay attention. 4.) The social media climate change movement is a form of green political practice.